ANALISIS KEPRIBADIAN DAN KONFLIK BATIN TOKOH UTAMA DALAM FILM PENDEK DÍ DÁ KARYA RYAN TAN - Putri Juita; Tantri Saraswati; Rudiansyah Rudiansyah (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2021)
This study discusses the analysis of the personality and inner conflict of the main character in Ryan Tan's short film Dí Dá . This study uses a qualitative descriptive method with a literature study based on Sigmund Freud's psychoanalytic theory with the personality structure of the id, ego, and superego. This study also uses the note-taking technique in collecting data. The purpose of this research is to analyze the personality structure and inner conflict of the main character in Ryan Tan's short film Dí Dá. The results obtained from this study are the main character's personalities are selfish, think that he is unlucky, and is full of regrets. The inner conflict experienced by the character is illustrated in the lyrics of the song he wrote which contains about how at first he felt unlucky and felt sorry for what he had done to his mother.